Multi-metal citrate complex: green synthesis using Lime juice for hydrogen storage applications - USHA RAJU; ANIL KUMAR (International Journal of Pharma and Bio Sciences, 2018)
Hydrothermal synthesis of four new multi metal-citrate metal-organic frameworks has been carried out through green synthetic pathways using lime juice as a source of citric acid. The obtained bright bluish green complexes are well defined crystalline solids with cubic geometry. The economical one pot synthesis is environment friendly and avoids the use and recovery of hazardous organic solvents used commonly in synthesis of metal-organic framework complexes. The lime juice squeezed from fresh fruit, used as a source of citric acid further reduces the time and cost involved in the extraction of citric acid commercially. The complexes thus obtained have been found to be of similar nature and comparable to those obtained by using commercially available citric acid. The complexes thus prepared are expected to reveal the potential applications in hydrogen storage for mobile applications as a green automobile fuel, as an optical material and in biomedical field. They have been characterized by Fourier transform infrared spectroscopy, Energy dispersive spectroscopy, UV-Visible spectroscopy, Differential scanning calorimetry, Fluorescence spectroscopy and Powder X - ray diffraction techniques. The surface morphology of complexes was studied using Scanning electron microscopy. Nitrogen adsorption-desorption measurements of Multi metal-citrates indicate high values of C constant, owing to strong adsorbate-adsorbent interaction because of open metal sites and active functionalities at the surface of these complexes and thus reveal high potential for hydrogen storage for mobile applications.